2017
DOI: 10.3892/ol.2017.6413
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of cofilin correlates with poor survival in breast cancer: A tissue microarray analysis

Abstract: Cofilin, a key regulator of actin cytoskeleton dynamics, is considered to be involved in cellular migration, tumor invasion and mitosis, and its activity is increased in cancer cells. To address the association between cofilin and breast cancer prognosis, which is unclear at present, cofilin expression was analyzed in tissue microarrays of tumors from 310 patients with breast cancer via immunohistochemistry. In a multivariate Cox regression analysis, a high expression of cofilin in tumor cells correlated signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Our findings are consistent with those of a report of cofilin expression being associated with pathological classification, lymph node metastasis, and clinical staging of esophageal cancer, which suggests that cofilin may be a new biomarker and therapeutic target for esophageal cancer diagnosis and prognosis . In another report by Maimaiti et al . who analyzed cofilin expression in tumors from 310 patients with breast cancer, it was suggested that cofilin was correlated with adverse outcomes and is therefore a potential prognostic factor for breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with those of a report of cofilin expression being associated with pathological classification, lymph node metastasis, and clinical staging of esophageal cancer, which suggests that cofilin may be a new biomarker and therapeutic target for esophageal cancer diagnosis and prognosis . In another report by Maimaiti et al . who analyzed cofilin expression in tumors from 310 patients with breast cancer, it was suggested that cofilin was correlated with adverse outcomes and is therefore a potential prognostic factor for breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…This might be one of the important aspects of the tumor immune escape mechanism. Interestingly, in recent years, some scholars have found that the expression of COF1 and P‐COF1 in breast cancer tissues is closely related to the prognosis of breast cancer patients, meaning that abnormal expression of COF1 might be a potential prognostic factor in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Ensley and others proposed that cofilin is significantly upregulated in several tumors and is associated with malignant progression; indeed, cofilin is considered a potential tumor biomarker and a molecular target for the treatment of bladder cancer [ 34 , 35 ]. In addition, high expression of cofilin in tumor cells is associated with shorter overall survival, indicating that it is a prognostic factor for tumors and can be used as a potential therapeutic target [ 36 , 37 ]. In the present study, we found that cofilin-2 was highly expressed in serum and tissue samples from patients with radiation-resistant NPC, while low serum and tissue levels were found in the radiosensitivity group.…”
Section: Discussionmentioning
confidence: 99%